Simplified approach for making risk decisions in a fast‐paced business environment. Issue 4 (21st June 2022) - Lu, Jianming; Lutostansky, Elizabeth M.
Abstract: For facilities where hazardous events of high consequences can happen, quantitative risk analysis (QRA) is used to determine whether the risk is tolerable against the risk criteria of the operating company or local regulations. Specific risk reduction measures may need to be defined and evaluated based on the QRA. A risk analysis considering both consequences and frequencies is typically time‐consuming and requires the collection of sufficient information regarding process, equipment, operation methods, weather, geographic conditions, the population, and so forth. Business management often requires prompt decisions in a fast‐paced business environment; therefore, the risk analysis must be done expediently to provide adequate information for business decisions. Some examples related to industrial gas facilities are summarized to show simplified analyses done to help define risk reduction measures and priorities in a shorter time frame than typically possible by using detailed quantitative risk assessment. Some generic methods for simplification are proposed.